Isolated tubal torsion in a woman who had laparoscopic tubal ligation by bipolar electrocoagulation [Bipolar elektrokoteri ile bilateral tuba ligasyonu olan kadında izole tubal torsiyon] - (:unkn) unknown (Marmara University, 2013)
A 29-year-old woman with tenderness in the left lower quadrant of the abdomen with no guarding or rebound tenderness was admitted to the hospital. Her pelvic examination revealed a tender, semi-mobile and semi-solid mass, 6 cm in diameter, just palpable adjacent to the left fornix. Her medical history was otherwise normal except that she had had laparoscopic tubal ligation by bipolar cauterization two months earlier. After 48 hours of medical treatment, laparoscopy was performed. The uterus and both ovaries appeared normal. The distal portion of the left tube remnant was twisted three times on its mesosalpinx and appeared gangrenous and necrotic. A left partial salpingectomy was done laparoscopically. The woman was discharged after 8 hours from the hospital. The pathology confirmed the diagnosis of torsion of a previously dilated tube.
Keywords: Laparoscopy; Tubal ligation; Tubal torsion